2008
DOI: 10.2319/110607-520.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Curing Lights on Microleakage under Bonded Lingual Retainers

Abstract: Objective: To evaluate the effects of high-intensity light curing units (light-emitting diode [LED] and plasma arc curing [PAC]) on the microleakage of flexible spiral wire retainers (FSWRs) at the composite/enamel and composite/wire interfaces. Materials and Methods: Forty-five human mandibular incisor teeth were separated into three groups of 15 teeth. Multistranded PentaOne wire of .0215 inch diameter was bonded to enamel and was cured with three different light curing units: a quartz-tungsten-halogen (QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Lingual retainer uygulamalar›nda kullan›lan materyallerin yüzey pürüzlülü¤ü ve sertli¤i, mikros›z›nt›, ba¤lan›m dayan›m› kuvveti gibi özellikleri ve farkl› ›fl›k kaynaklar›n›n bu materyallerin bu özellikleri üze-rine etkisi etkisi önceki birçok çal›flmada araflt›r›lm›flt›r (9,(14)(15)(16)(17)(18)(19)(20). Schulz ve arkadafllar› (21) üç fakl› rezin sisteminin içine tel yerlefltirerek bond dayan›kl›l›¤›n› araflt›r-m›fllard›r.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Lingual retainer uygulamalar›nda kullan›lan materyallerin yüzey pürüzlülü¤ü ve sertli¤i, mikros›z›nt›, ba¤lan›m dayan›m› kuvveti gibi özellikleri ve farkl› ›fl›k kaynaklar›n›n bu materyallerin bu özellikleri üze-rine etkisi etkisi önceki birçok çal›flmada araflt›r›lm›flt›r (9,(14)(15)(16)(17)(18)(19)(20). Schulz ve arkadafllar› (21) üç fakl› rezin sisteminin içine tel yerlefltirerek bond dayan›kl›l›¤›n› araflt›r-m›fllard›r.…”
Section: Discussionunclassified
“…Forthe materials used in lingual retainer fabrication, the properties such as surface roughness and hardness, microleakage, shear bond strength (SBS) and the effects of different light sources on these properties were investigated in previous studies (9,(14)(15)(16)(17)(18)(19)(20) (23) evaluated six different bonded lingual retainer wire/composite combinations' initial bond strengths. However, as far as we search in orthodontic literature no study which will investigate SBS of lingual retainer adhesives, minimizing the effects of other contributing factors such as surface shape of experimental tooth, wire/composite combination etc., was found.…”
Section: Gereçler Ve Yöntem öRneklerin Haz›rlanmas›mentioning
confidence: 99%
“…However, high‐intensity light‐curing units allow more microleakage at the composite–wire interface, and might not be safe for the bonding of lingual retainers. A comparison of the results showed the least microleakage with quartz tungsten halogen (mean: 1.10 ± 1.05 mm), and the greatest microleakage with PACL units (mean: 2.63 ± 1.49 mm) . Arikan et al .…”
Section: Microleakagementioning
confidence: 96%
“…Baysal et al . studied microleakage under lingual retainers bonded on extracted mandibular incisors using high‐intensity curing lights, and found that little or no microleakage occurs at the composite/enamel interface with high‐intensity light‐curing units . However, high‐intensity light‐curing units allow more microleakage at the composite–wire interface, and might not be safe for the bonding of lingual retainers.…”
Section: Microleakagementioning
confidence: 99%
“…13 Previous studies revealed higher marginal adaptation and reduced microleakage formation and lower material deflection when silorane-based materials were used compared to methacrylate composites. 14,15 In the orthodontic literature, different band cements, 16 light sources, 17,18 composites and brackets [19][20][21][22][23] have been evaluated for microleakage but these studies primarily focused on enamel demineralization. The FSWRs are intended to serve for a long time in the mouth and are exposed to various chemical and mechanical degradation.…”
Section: Introductionmentioning
confidence: 99%